2022
DOI: 10.3390/en15176435
|View full text |Cite
|
Sign up to set email alerts
|

An Offline and Online Approach to the OLTC Condition Monitoring: A Review

Abstract: Transformer failures have a significant cost impact on the operation of an electrical network. In many utilities, transformers have been operating for many years past their expected usable life. As power demand has surged, transformers in some areas are being loaded beyond their rated capacity to meet the demand. One of the vital components in a transformer is the on-load tap changer (OLTC), which regulates the voltage in the distribution network. This study aims to review several condition-monitoring techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Among the power transformer components, the On-Load Tap Changer (OLTC), which is used to regulate the transformer's output voltage, is identified as one of the most vulnerable parts. Its failure is among the main cause of major power transformers' catastrophic failures [3][4][5][6]. In this regard, it is necessary to detect OLTC faults in their incipient stages.…”
Section: Introductionmentioning
confidence: 99%
“…Among the power transformer components, the On-Load Tap Changer (OLTC), which is used to regulate the transformer's output voltage, is identified as one of the most vulnerable parts. Its failure is among the main cause of major power transformers' catastrophic failures [3][4][5][6]. In this regard, it is necessary to detect OLTC faults in their incipient stages.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, if the voltage difference between the nodes becomes sufficiently large, there is a risk of overvoltage at bus 2. All voltage regulation methods involve changing one or more of the variables included in Equation (6). The basic and conventional method of voltage regulation in distribution networks is based on influencing the voltage at the main bus of the feeder, i.e., 𝑉 .…”
Section: Introductionmentioning
confidence: 99%
“…It is a cost-effective method, because most HV/MV transformers are equipped with an OLTC. Its disadvantages undoubtedly include a slow response time, including a lack of ability to regulate the voltage during transients, together with restricted tap changes each day due to the limited mechanical endurance of the OLTC [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An On-Load Tap-Changer (OLTC) is one of the most important components of the power transformer and it is used to regulate the transformer voltage by changing the number of turns in one winding of the transformer (turns ratio). It is reported that around 30% of transformer faults are due to OLTC failures, hence the requirement for a timely condition assessment of this component [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%